Re: pairing Louise Bourgeois: sculpture and psychoanalysis in the years 1946 -1969 - Cohen, Andrea Sue Michelle (My University, 2016)
The early part of this dissertation is concerned with a particular period (1946-‐1969) in sculptor Louise Bourgeois’ life when her artistry and her psychoanalysis overlapped for the first time. Within this time frame, the years 1952 – 1969 reference a particular period when she was in deep psychoanalysis with Dr. Henry Lowenfeld, a period, which profoundly affected her self understanding and associated art practice. By establishing her positioning within a story of Modernism (as a departure point) I will then go on to consider how the more traditional historical readings of her work can be used to understand her work and behavior within a more pronounced psychoanalytic frame. From this positioning I will reconsider Bourgeois’ artistic practice as being deeply linked to an unconscious need to repair early psychic ruptures with maternal and paternal caretakers. From a Kleinian position I will foreground Bourgeois’ predisposition to sculpt as a reparative enactment driven by her primary internal Object-‐Relations. Key works and free-‐associative written material (composed in relation to her psychoanalytic sessions from the outlined time frame) will provide evidence for her psychic shifts over the period. These will be investigated in relation to changes in her sculptural output -‐ key signifiers of repressed psychic experience, becoming conscious. The dissertation seeks to understand the relationship between these two investigative processes (art and psychoanalysis). Similarly, with reference to Bourgeois, the latter half of this project will investigate my personal (parallel) experience as a sculptor and analysand1 . In relation to both enquiries, I will specifically consider the therapeutic relationship between the physical act of making artworks and the verbal psychoanalytic experience. In an effort to understand how the pairing of these two communicative modalities might impact artistic experience.
Thesis (M.A. (Fine Arts))--University of the Witwatersrand, Faculty of Humanities, School of Arts, 2016.
Keywords: Bourgeois, Louise, 1911-2020--Psychology; Psychoanalysis and art